Pengaruh Formulasi Tinta Ungu Organik Berbahan Dasar Ubi Ungu terhadap Ketahanan Cahaya pada Cetak Saring - Subhan Zuhri Ritonga; Rachmah Nanda Kartika; Yoga Putra Pratama (Pusat riset dan Inovasi Nasional, 2025)
This study aims to evaluate the lightfastness of organic ink formulated from purple sweet potato (Ipomoea batatas L.) pigment for screen-printing applications on 24s cotton combed fabric. The ink formulations varied the pigment amount (10, 15, and 20 grams) and solvent volume (distilled water) of 25 and 30 mL, while the binder and thickener components were kept constant. Lightfastness was assessed by measuring the change in lightness (ΔL*) before and after 24 hours of light exposure. The results showed that the formulation containing 15 g of pigment and 25 mL of solvent (P2A1) exhibited the best colorfastness, with an average ΔL* of 0.23, while the formulation with 10 g pigment and 25 mL solvent (P1A1) showed the poorest performance (average ΔL* of 1.86). A lower solvent volume resulted in higher resistance to light exposure. Moreover, using either too little or too much pigment negatively affected ink transfer and reduced lightfastness. Two-way ANOVA on log-transformed data revealed that the interaction between pigment concentration and solvent volume had a significant effect on ΔL* (p < 0.001), contributing 72.8% to the total data variation. This study confirms that achieving an optimal balance between pigment amount and solvent volume is crucial for producing organic ink with good lightfastness